Plasmodium falciparum Merozoite Associated Armadillo Protein (PfMAAP) Is Apically Localized in Free Merozoites and Antibodies Are Associated With Reduced Risk of Malaria - Aniweh, Yaw; Nyarko, Prince B.; Charles-Chess, Essel; Ansah, Felix; Osier, Faith H. A.; Quansah, Evelyn; Thiam, Laty Gaye; Kamuyu, Gathoni; Marsh, Kevin; Conway, David J.; Tetteh, Kevin K. A.; Awandare, Gordon A. (Frontiers in Immunology, 2020)
Understanding the functional role of proteins expressed by Plasmodium falciparum is an important step towards unlocking potential targets for the development of therapeutic or diagnostic interventions. The armadillo (ARM) repeat protein superfamily is associated with varied functions across the eukaryotes. Therefore, it is important to understand the role of members of this protein family in Plasmodium biology. The P. falciparum armadillo repeats only (PfARO; Pf3D7_0414900) and P. falciparum merozoite organizing proteins (PfMOP; Pf3D7_0917000) are armadillo-repeat containing proteins previously characterized in P. falciparum. Here, we describe the characterization of another ARM repeat-containing protein in P. falciparum, which we have named the P. falciparum Merozoites-Associated Armadillo repeats protein (PfMAAP). Antibodies raised to three different synthetic peptides show apical staining of free merozoites and those within the mature infected schizont. We also demonstrate that the antibodies raised to the PfMAAP peptides inhibited invasion of erythrocytes by merozoites from different parasite isolates. In addition, naturally acquired human antibodies to the N- and C- termini are associated with a reduced risk of malaria in a prospective cohort analysis.